Effect of urinary angiotensinogen and high-salt diet on blood pressure in patients with chronic kidney disease: results from the Korean Cohort Study for Outcome in Patients with Chronic Kidney Disease (KNOW-CKD) - Kim, Ha Yeon (Korean J Intern Med, 2021)
BACKGROUND/AIMS: This study aimed to investigate whether urinary angiotensinogen (UAGT) excretion was associated with elevated blood pressure in patients with chronic kidney disease (CKD) and to evaluate the relationship among blood pressure, intra-renal renin-angiotensin system (RAS) activity, and dietary sodium in patients with CKD. METHODS: Participants from the Korean Cohort Study for Outcome in Patients with Chronic Kidney Disease (KNOW-CKD) were included. Of the total cohort of 2,238 individuals with CKD, we included 1,955 participants who underwent complete 24-hour urinary sodium (24-hour UNa) analysis. They were categorized into three groups according to three tertiles of their 24-hour UNa, reflecting daily salt intake. To measure intra-renal RAS activity, the UAGT excretion was assayed with an enzyme-linked immunosorbent assay. RESULTS: Elevated 24-hour UNa levels, logarithm of UAGT-to-creatinine ratio (UAGT/Cr), increased waist-to-hip ratio, and decreased estimated glomerular filtration rate were the risk factors for increased systolic blood pressure. Systolic blood pressure showed a positive correlation with 24-hour UNa levels and logarithm of UAGT/Cr. CONCLUSIONS: UAGT and urinary sodium excretion are independent determinants of systolic blood pressure in patients with CKD. These findings suggest that increased systolic blood pressure in CKD patients is associated with both increased dietary sodium levels and intra-renal RAS activity. The risk of elevated systolic blood pressure in the 3rd tertile of both the UAGT/Cr and 24-hour UNa groups was about 2.3 times higher than that in the reference group.